The association of maternal risk factors to macrosomia in rural areas of Haryana, India: a community based study - Malik, Manisha; Khanna, Pardeep; Verma, Ramesh (International Journal Of Community Medicine And Public Health, 2018)
Background: Macrosomia affects 1-10% of all pregnancies. The macrosomia is reportedly associated with neonatal morbidity, neonatal injury, maternal injury and cesarean delivery. The present study was aimed at finding out prevalence and assessing association of maternal risk factors with macrosomia. Methods: This community based retrospective and cross-sectional study was carried out in 23 rural sub-centres of block Beri, district Jhajjar (Haryana, India) among 920 mothers. A predesigned pretested semistructured questionnaire was used to collect information. Univariate analysis along with logistic regression analysis was performed. Results: The prevalence of macrosomia among live births was 1.3% (n=12). In the present study, mothers from upper and upper middle socio-economic status had six times higher odds of delivering a large baby. Diabetic mothers had seventeen times higher incidence of macrosomia as compared to non-diabetic mothers. Mothers who consumed full course of iron folic acid (IFA) tablets during antenatal period had 24% lesser chances of macrosomia in live births as compared to mothers who did not consume the full course. Conclusions: The findings of the present study emphasize that incidence of macrosomia can be reduced by strengthening antenatal monitoring, prevention of complications, early diagnosis and appropriate and adequate management of treatable risk factors in mothers.